2018
DOI: 10.7717/peerj.5111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the toxic effects of different mycotoxins on porcine and mouse oocyte meiosis

Abstract: BackgroundAflatoxin B1 (AFB1), deoxynivalenol (DON), HT-2, ochratoxin A (OTA), zearalenone (ZEA) are the most common mycotoxins that are found in corn-based animal feed which have multiple toxic effects on animals and humans. Previous studies reported that these mycotoxins impaired mammalian oocyte quality. However, the effective concentrations of mycotoxins to animal oocytes were different.MethodsIn this study we aimed to compare the sensitivity of mouse and porcine oocytes to AFB1, DON, HT-2, OTA, and ZEA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…OTA affected oocyte maturation only at micromolar concentrations. These findings are in agreement with previously reported studies in mice (Huang and Chan 2014 ; Jia et al 2019 ) and pigs (Lu et al 2018 ). However, data on meiosis progression with effects on earlier meiotic stages were not reported in those studies.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…OTA affected oocyte maturation only at micromolar concentrations. These findings are in agreement with previously reported studies in mice (Huang and Chan 2014 ; Jia et al 2019 ) and pigs (Lu et al 2018 ). However, data on meiosis progression with effects on earlier meiotic stages were not reported in those studies.…”
Section: Discussionsupporting
confidence: 94%
“…This result was unexpected since mouse oocytes exposed to OTA during IVM exhibited impaired embryonic development (Huang and Chan 2014 ; Jia et al 2019 ). A possible explanation for these discrepancies may lie in species-specific effects (Lu et al 2018 ). At any tested concentration, OTA did not affect blastocyst morphology and growth and, increased the apoptotic index only at nanomolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on porcine oocytes have shown that 10 μ M ZEA significantly affects oocyte maturation (Lu et al, 2018). Therefore after parthenogenetic activation, we first examined the effects of 5 or 10 μM ZEA treatment on embryonic development.…”
Section: Resultsmentioning
confidence: 99%
“…PPT has been shown to cause oxidative stress and apoptosis in porcine oocytes (Jiang et al, 2020). Mycotoxins, such as AFB1, deoxynivalenol, and HT-2 toxins, could also cause oxidative stress in oocytes and other cell types (Yang et al, 2014;Zhang et al, 2016;Lu et al, 2018). In addition, the excessive accumulation of histone H2A variant H2AX in cells undergoing DNA damage can increase the activity of NADP (H) oxidase (NOx), thereby increasing the level of ROS.…”
Section: Discussionmentioning
confidence: 99%